Pembangunan Sistem Informasi Pelaporan Masalah Lingkungan Berbasis Web di Universitas Kristen Satya Wacana - Wijaya, Yemima Clara; Setiyawati, Nina (Jurnal Indonesia : Manajemen Informatika dan Komunikasi, 2024)
Meeting environmental challenges necessitates the exploration of new and inventive solutions. The Environmental Quality Index (IKLH) report revealed an uptick in Indonesia's index to 72.42 in 2022 from 71.45 in 2021, despite a worsening air quality trend. Acknowledging the importance of Human Resource Management and "Go Green" education in promoting environmental consciousness, this paper proposes the adoption of Laravel for expeditious handling of environmental issues at UKSW. Through the utilization of the Waterfall model and UML methodology, the system integrates MVC architecture, streamlining the process of environmental problem reporting for students. Rigorous Black Box Testing ensures the seamless functionality of the system. Ultimately, this initiative seeks to fortify the university's environmental stewardship while advancing the Go Green campaign, thereby fostering a campus environment that is both pristine and sustainable.